(untitled) (Journal of Medicine, 2014)
Natural fluidity of movement & feelings seem to be lost in PD. Automatic activities of facial expression, swallowing, speaking, walking become less automatic. Clinical experience is essential to diagnose, decide symptom worsening, determine end of dose wearing off & the on-off states, acknowledge non-motor problems, titrate dopaminergic treatment & add adjunctive treatment. Current breakthroughs in the treatment concepts like discovery of non-dopaminergic brain targets, neuroplasticity, L-DOPA formulations including Levodopa/carbidopa intestinal gel[LCIG], pump therapies, deep brain stimulation have been discussed. LCIG is available in some 30 countries but cost makes it prohibitive for widespread use. Goalbased motor skill training improves cognitive & automatic components of motor control in mild to moderate PD. Levodopa + carbidopa, remains the gold standard & eventually leads to L-DOPA induced dyskinesia in the majority within 10 years of treatment. MAO-B inhibitors have an excellent side effect profile but mild motor benefit. Dopamine agonists (nonergot-ropinirole, pramipexole) provides moderate symptomatic benefit and delay the development of dyskinesia but at the expense of psychiatric and nonmotor side effects. DOI: http://dx.doi.org/10.3329/jom.v14i2.19670 J Medicine 2013, 14(2): 174-184